A Comparative Study on Efficiency Assessment between Public and Private Universities: Evidence from Tanzania (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2014)
Our study builds on a two- stage Data Envelopment Analysis to examine and compare the efficiency of public and private universities in Tanzania in 2008-2012. First, we use data envelopment analysis to measure the technical and scale efficiency of universities. Secondly, we examine factors that influence efficiency through Tobit regression model for both public and private Universities. The findings from the model affirm that the efficiency of the two University categories varies significantly. However, public University average efficiency is observed to be higher than that of private Universities. Whereas public Universities are inefficient in research and publications, private universities efficiency is determined by enrolment, academics staff and consultancy services. Given the contemporary significance of University education to social and individual development, we plead to the government University agency (TCU) to review the entire quality assurance process to improve Universities efficiency.